Aplikasi Prefabricated Vertical Drain (PVD) Untuk Stabilisasi Tanah Dasar Pada Proyek Pembangunan Jalur Ganda Kereta Api Di Km 437+300 Sampai Km 438+500 Gombong, Kebumen - Prativi, Ayu; Astuti, Septiana Widi; Ependi, Ahmad (Politeknik Perkeretaapian Indonesia Madiun, 2019)
The subgrade in the railway double track development project in KM 437 + 300 to KM 438 + 500 Gombong, Kebumen is soft land (N-SPT <15) so that it requires efforts to improve the land to avoid land subsidence exceeding the allowable land subsidence, which is equal to 20cm In this research, an effort to repair subgrade uses Prefabricated Vertical Drain (PVD) to accelerate the process of soil congestion due to the load of the railroad pile, the burden of railroad construction, and the burden of the passing railroad. Compression analysis results show that the subgrade will experience a land subsidence of 0.524m. The natural consolidation time needed to achieve a 90% degree of consolidation is 268.9 years. Meanwhile, the time of consolidation to reach a degree of consolidation of 90% using PVD spaced 0.8 m with a triangle and quadrilateral pattern is for 15 weeks and 18 weeks. Planting PVD in both patterns is as deep as 24 m